The Characteristics of Human Resources and Related Research Activities among Basic Stem Cell Research Groups in China - Sheng-Jun WANG; Li-Juan LIU; Guang-Yue JI; Xiao-Hua (Andrew); Tian-Jiao JIANG; Mei-Hua LU; De-Lin YU; Qiang GUO; Jin-Hai SUN (Tehran University of Medical Sciences, 2019)
Background: This study aimed to evaluate the characteristics of faculty and research activities of basic stem cell research groups in China. Methods: A questionnaire was administered to persons who knew the information among 46 basic stem cell research groups in China. Multiple linear regression models and repeated-measures analyses of variance were used. Repeated-measures analyses of variance were used. Results: Of the 46 groups, 39.1% did not have any faculty recruited from abroad from 2009 to 2013, 37.0% did not have any faculty with junior-level title, 34.8% had ≤25.0% faculty with either M.D. or Ph.D. degree. Papers published in SCI journals per faculty and having faculty recruited from abroad were positively associated with research funding per faculty. The groups with faculty recruited from abroad had significantly higher research funding per faculty over time compared with the group without faculty recruited from abroad. Repeated-measures analyses of variance showed the group with faculty recruited from abroad had significantly higher research funding per faculty over time compared with the group without faculty recruited from abroad. Conclusion: To increase the development of basic stem cell research, some characteristics of human resources should be improved, and the groups should recruit more faculty with overseas experience.